Partner in crime - Jance, Judith A., 1944- (Avon suspense ., 2003)
The dead woman on a cold slab in the Arizona morgue was a talented artist recently arrived from the West Coast. The Washington State Attorney General's office thinks this investigation is too big for a small-town female law officer to handle, so they're sending Sheriff Joanna Brady some unwanted help -- a seasoned detective named Beaumont. Sheriff Brady resents his intrusion, and Bisbee, Arizona, with its ghosts and memories, is the last place J.P. Beaumont wants to be. But the twisting desert road they must reluctantly travel together is leading them into a very deadly nest of rattlers. And if they hope to survive, suddenly trust is the only option they have left...